Typhonium flagelliforme as a Cancer Prevention Plant-Based on In Vitro, In Vivo and Bioinformatics Research Method: A Systematic Literature Review - Teddy Siswanto; Ratna Shofiati; Ismi Hasnatul Afifah (Future Science)
The development of cancer-preventing plant research develops along with the development of science and information technology. The purpose of this study was to collect research related to the Typhonium flagelliforme plant so that it can be used to add to the research literature that synergizes with multi-scientific disciplines. This research method uses a Study Literature Review from the journals Proquest, ScienceDirect, NCBI, and other journals since 2012 with the keywords Typhonium flagelliforme or Rodent Tuber or Keladi-tikus to identify the type of research In Vitro, In Vivo and Bioinformatics and search by journal publisher category. The results of the Systematic Literature Review research obtained a total of 194 papers and after being traced from the abstract, then 51 papers were selected consisting of 42 In Vitro research papers, 1 In Vivo paper and 6 Bioinformatics papers, and a combination of In Vitro and In Vivo papers totaling 2 papers. Meanwhile, based on scientific fields the most are from Natural Science, Medicine, Bioinformatics, and Pharmacy. Based on the results of research identification, further research is proposed for Typhonium flagelliforme as a plant that has the potential to prevent cancer, can involve researchers from different scientific families so that it is suitable for multi-disciplinary research by synergizing the three methods of In Vitro, In Vivo and Bioinformatics through the involvement of researchers from Biology, Chemistry, Medicine, Pharmacy and Informatics to get further research depth.